Approval voting without ballot restrictions. Issue 3 (26th July 2021) - Ceron, Federica; Gonzalez, Stéphane
Abstract : We axiomatically study voting rules without making any assumption on the ballots that voters are allowed to cast. In this setting, we characterize the family of "endorsement rules, " which includes approval voting and the plurality rule, via the imposition of three normative conditions. The first condition is the well known social‐theoretic principle of consistency ; the second one, unbiasedness, roughly requires social outcomes not to be biased toward particular candidates or voters; the last one, dubbed no single voter overrides, demands that the addition of a voter to an electorate cannot radically change the social outcome. Building on this result, we provide the first axiomatic characterization of approval voting without the approval balloting assumption. The informational basis of approval voting as well as its aggregative rationale are jointly derived from a set of conditions that can be defined on most of the ballot spaces studied in the literature.